(untitled) (Nordic Journal of African Studies, 2000)
This article studies the teaching of mathematics in bilingual education in the Bambara-speaking town of Ségou. The bilingual principles of convergent pedagogy are examined in the light of teaching material, teacher training and classroom practice. It shows that neither the textbooks nor the training enable the teachers to follow the pedagogical principles that have been laid down, and that the transition from Bambara to French, which takes place in the 4th grade as far as mathematics is concerned, still represents a great problem in the 5th grade. However, the fieldwork, which took place in 1997, revealed an interesting method that seemed to be a local invention. Building on the Bambara play of riddles, different groups challenge each other both in creating and solving mathematical problems, and the children participate eagerly in this game. This type of teaching fits in well with active pedagogy and could be introduced into convergent pedagogy at a general level.